A Mechanism for the Midwinter Minimum in North Pacific Storm‐Track Intensity From a Global Perspective. Issue 5 (10th March 2020) - Park, Mingyu; Lee, Sukyoung
Abstract: The midwinter minimum in North Pacific storm‐track intensity is a perplexing phenomenon because the associated local baroclinity in the North Pacific is maximum during midwinter. Here, a new mechanism is proposed wherein the midwinter minimum occurs in part because global planetary‐scale waves consume the zonal available potential energy, limiting its availability for storm‐track eddy growth. During strong midwinter suppression years, the midwinter minimum is preceded by anomalously large planetary‐scale eddy kinetic energy and subsequent reduction in zonal available potential energy and global baroclinity. Consistent with previous studies, this large planetary‐scale eddy kinetic energy takes place after enhanced Pacific warm pool convection, which peaks during winter. These results indicate that the midwinter minimum is in part caused by heightened warm pool convection, which, through excitation of planetary‐scale waves, leads to a weaker storm‐track. This finding also helps explain the existence of the midwinter North Atlantic storm‐track minimum. Plain Language Summary: During boreal winter, midlatitude storms are concentrated in two regions, one over the North Pacific Ocean and the other over the North Atlantic Ocean. These regions of enhanced storm activity are referred to as storm tracks. These storms are fed by the potential energy associated with the north‐south temperature gradient. This energy is known as zonal available potential energy (ZAPE). The north‐south temperature gradient upstream of the Pacific storm track undergoes a seasonal cycle, reaching its maximum during midwinter. Therefore, the intensity of the Pacific storm track is expected to reach its greatest strength during midwinter. However, the Pacific storm‐track strength exhibits a local minimum during midwinter. Therefore, this phenomenon has been a subject of active research for decades. Most studies have investigated factors that are local to the Pacific storm track. Here, a new mechanism with a global perspective is presented. The main finding is that convection over the tropical western Pacific reaches its maximum strength during December, and this convection generates planetary‐scale waves that consume ZAPE, leaving less ZAPE behind for the storms to feed upon. This global perspective also helps to explain the existence of the midwinter North Atlantic storm‐track minimum, which was discovered more recently. Key Points: The minimum in storm‐track activity during midwinter can be observed globally The midwinter minimum is preceded by an enhancement of planetary‐scale wave growth and a reduction of zonal available potential energy The planetary‐scale wave growth and the zonal available potential energy decline follow an enhanced zonal asymmetry in tropical convection